KESEMPATAN BERTUMBUH DAN MANAJEMEN LABA: UJI POLITICAL COST HYPOTHESIS - Susilawati, R. Anastasia Endang (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2010)
In this paper, we test political cost hypothesis in Indonesian market. Political cost hypothesis said that some firms that are more vulnerable to political cost than the others manage income downward to avoiding the attention of government and regulator. In this context we evaluate firms with high investment opportunity set (IOS). Firm with high IOS faces more political cost than firm with low IOS. So it is hypotesized that they will be lowering income to minimize the political cost, like increasing demand of labor union, government intrusion, antitrust regulator and the other. Consistent with previous study, we find that firm with high investment opportunity set manage accrual downward to counter the potential government intrusions and to reduce the political cost.